1113 Physical Activity Moderates The Sleep-emotional Distress Relationship, But Less So Among Blacks Vs. Whites. (27th May 2020) - Moore, J; Williams, N; Chung, D; Parra, Y; Jean-Louis, G; Seixas, A
Abstract: Introduction: Emotional distress (ED) is associated with poor sleep. Research shows that minority populations experience greater vulnerabilities to both ED and poor sleep. Interventions such as relaxation training and behavioral therapy address this relationship but are not always successful. Research shows that physical activity (PA) is negatively associated with ED and positively associated with sleep duration. However, it is unclear whether PA attenuates the relationship between ED and sleep, and if this relationship differs by race/ethnicity. Methods: We analyzed data from the 2005-2015 National Health Interview Survey (NHIS), a nationally representative dataset of 416, 152 participants. ED, hours of PA per day, and average sleep duration were collected. Regression models with covariates (age, sex, employment status, BMI) were used to analyze the moderation effect of PA within sleep and ED. Regression models were stratified by race/ethnicity. Results: 261, 686 participants (45, 926 blacks, 17.55%, and 215, 760 whites, 82.45%) responded with the required variables for analysis. 63% of participants reported at least some physical activity. The results of the regression showed that a significant amount of variance in ED stemmed from sleep duration; F (7, 121088) = 1, 619.72, p < 0.001. PA was found to have a significant main effect, t (121, 088) = 9.01, p = <0.001. There was a significant moderation effect of PA, t (121088) =7.26, p < 0.001. Stratification showed that the moderation effect of PA was not significant among blacks t (121, 088) = -1.45, p =0.149 and significant among whites b = -.08, t (101, 754) = -7.82, p < 0.001. Conclusion: The present study found support for moderation of PA in the sleep-ED relationship. However, it found that blacks do not experience the same benefits of PA in this relationship as whites. Further research should be performed to understand the connection of PA to sleep duration and ED. Support: This study was supported by funding from the NIH: R01MD007716, R01HL142066, R01AG056531, K01HL135452, and K07AG052685